Role of Institutional Interaction for Financial Stability in the context of Inflation Targeting - El HIRI, Abderrazak; habiby, salwa (Advances in Social Sciences Research Journal, 2018)
The Moroccan authorities are aiming for the implementation of an inflation targeting policy. However, the economy has a number of handicaps, including a high level of debt and modest financial stability. The purpose of this article is to analyze how the interaction between institutions could enhance financial stability and manage risks that could disrupt the smooth functioning of the market as part of an inflation-targeting regime, across two empirical studies. After studying the interaction between policies, we have developed a model of structural equations that integrates the specificities of the Moroccan economy and its institutions into a predictive vision. We found that the weight of debt influences negatively the financial market, but an application of inflation targeting can mitigate the severity of the financial and debt crisis on financial stability while keeping inflation and production close to their objectives. The results of this study encourage the transition in a medium-term to inflation targeting policy, since reducing the level of debt influence positively the expectations of economic agents.